Ultrarapid Insulin Use Can Reduce Postprandial Hyperglycemia and Late Hypoglycemia, Even in Delayed Insulin Injections: A Connected Insulin Cap-Based Real-World Study - Gómez-Peralta, Fernando; Valledor, Xoan; López-Picado, Amanda; Abreu, Cristina; Fernández-Rubio, Elsa; Cotovad, Laura; Pujante, Pedro; García-Fernández, Elena; Azriel, Sharona; Corcoy, Rosa; Pérez-González, Jesús; Ruiz-Valdepeñas, Luis (Diabetes Technology & Therapeutics, 2024)
Objectives: Reaching optimal postprandial glucose dynamics is a daily challenge for people with type 1 diabetes (T1D). This study aimed to analyze the postprandial hyperglycemic excursion (PHEs) and late postprandial hypoglycemia (LPH) risk according to prandial insulin time and type. Research Design and Methods: Real-world, retrospective study in T1D using multiple daily injections (MDI) analyzing 5 h of paired continuous glucose monitoring and insulin injections data collected from the connected cap Insulclock®. Meal events were identified using the rate of change detection methodology. Postprandial glucometrics and LPH (glucose <70 mg/dL 2–5 h after a meal) were evaluated according to insulin injection time and rapid (RI) or ultrarapid analog, Fiasp® (URI), use. Results: Meal glycemic excursions (n = 2488), RI: 1211, 48.7%; UR: 1277, 51.3%, in 82 people were analyzed according to injection time around the PHE: −45 to −15 min; −15 to 0 min; and 0 to +45 min. In 63% of the meals, insulin was injected after the PHE started. Lower PHE was observed with URI versus RI (glucose peak-baseline; mg/dL; mean ± standard deviation): 106.7 ± 35.2 versus 111.2 ± 40.3 (P = 0.003), particularly in 0/+45 injections: 111.6 ± 40.2 versus 118.1 ± 43.3; (P = 0.002). One third (29.1%) of participants added a second (correction) injection. The use of URI and avoiding a second injection were independently associated with less LPH risk, even in delayed injections (0/+45), (−36%, odds ratio [OR] 0.641; confidence interval [CI]: 0.462–0.909; P = 0.012) and −56% (OR 0.641; CI: 0.462–0.909 P = 0.038), respectively. Conclusions: URI analog use as prandial insulin reduces postprandial hyper- and hypoglycemia, even in delayed injections.
Keywords: insulin; Postprandial Hyperglycemia; Hypoglycemia; study; Scopus